Marriage and fertility in China and Japan - Chen, M (2018)
Declining family formation among women and closely related trends such as postponed marriages, rising age at first childbirth, and low fertility rates have been observed in modern China and Japan. In this light, understanding the determinants of women’s marriage and fertility decisions carries important sociological and policy implications. However, most of the extant research is impeded by lack of theory and a poor understanding of local cultural and institutional contexts. Existing research largely involves generating statistical relationships between socioeconomic status related variables and family formation outcomes. This methodology is insufficient for explaining the phenomenon in China and Japan where family formation is also influenced by context-specific factors such as gendered norms in the family and workplace. There is also a knowledge gap on how the relationships between these variables varies across China and Japan, which have had undergone similar but non-identical economic and demographic transformations. I use data from the Chinese General Social Survey, the Japanese Social Stratification and Mobility Survey, the East Asia Social Survey, and the Panel Study of Family Dynamics to address the following questions: 1) How do son preference, co-residence with parents and education affect women’s second births in China? 2) How are the labour market conditions of women and their husbands at the point of marriage associated with women’s transition to motherhood in Japan? 3) How do parental roles in the matching process change women’s family formation decisions in China and Japan? The key findings are that firstly, context-specific factors, such as son preference in China, have a large and significant effect on family formation. Secondly, other parties, such as parents, play an important role in women’s family formation in these societies. Thirdly, there is a substantial degree of heterogeneity in the way that these factors contribute to family formation in China and Japan.